2010
DOI: 10.1111/j.1365-2214.2010.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness of left‐behind children: a cross‐sectional survey in a sample of rural China

Abstract: Left-behind children are at significant risk for loneliness. More specific investigations targeted towards the psychological well-being of these children are needed to identify the underlying preventable risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
144
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(159 citation statements)
references
References 13 publications
12
144
2
1
Order By: Relevance
“…Previous literature has suggested that left-behind children may be at greater risk of depression, anxiety, and loneliness as a result of separation from their parents. 27,28 Compared with children living with both parents, the leftbehind children are also reported to have lower levels of satisfaction with life, including lower levels of happiness and quality of life. 29,30 Study Results…”
Section: On December 18 2016 By Hw Teammentioning
confidence: 99%
“…Previous literature has suggested that left-behind children may be at greater risk of depression, anxiety, and loneliness as a result of separation from their parents. 27,28 Compared with children living with both parents, the leftbehind children are also reported to have lower levels of satisfaction with life, including lower levels of happiness and quality of life. 29,30 Study Results…”
Section: On December 18 2016 By Hw Teammentioning
confidence: 99%
“…7 Therefore, rural migrants usually have to travel on their own to seek job opportunities in cities, leaving their children at home (Brown 2006;Chen et al 2009). 8 According to an authoritative survey report by All-China Women Federation (Jia and Tian 2010), the estimated number of left-behind children in rural areas reached nearly 58 million in 2008, a figure that represents almost 30% of all rural children in China.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that as compared with their non-left-behind peers, left-behind children were more likely to suffer from a high level of loneliness, life dissatisfaction, and unhappiness (Jia and Tian, 2010;Jordan and Graham, 2012;Su et al, 2013). However, there has been a lack of study exploring the influence of parental absence on children's academic performance among the left-behind children.…”
mentioning
confidence: 99%